New e-learning objects for the mathematics courses from engineering degrees : design and implementation of question banks in Maple T.A. using LaTeX - Pereira, Rui M. S. (2010)
Mathematics at an undergraduate level is frequently presented to the students in quite a traditional way. When implementing the Bologna education reform in Portuguese universities, the number of contact hours of the courses decreased (considerably in some cases), therefore increasing the need of a more self-responsible learning by the student. This means that the student has to work by himself (i.e., outside lectures and examples classes) on a regular basis. In practice this implies that the lecturer is supposed to plan the students work, in principle weekly basis. In this paper we intend to describe an experience made at the Department of Mathematics for Science and Technology of the University of Minho in Portugal. Using an e-learning platform specially designed for teaching Mathematics called Maple T. A., we designed, programmed and made available for the students various sets of exercises organized in Question Banks on the course of Calculus. We also make a comparison of alternative ways to program the questions of a questions bank. The advantage of this platform is that if properly designed, the questions can be always different and with different methods of solving (because of the use of random variables), the student can do it whenever and wherever he is (he does it via internet) and it feedback is made available to the students as soon as he submits the exercise. At the end of the academic year and with the aim of being able to evaluate how did the students feel about this experience, the students were given a survey implemented on the elearning platform. The results obtained from this survey strongly suggest, among other things, that using Maple T.A. helped the students in the study of the course of Calculus, and that it helped to achieve better results on the course.